Bi-Directional Waterway Reveals Nutrient Runoff From Cropland - Ozbay, Gulnihal; Stone, Matthew (Frontiers in Environmental Science, 2018)
Blackbird Creek is the waterway that empties into the Delaware Bay. The lower 21 km of the creek has been shown to have appreciable salinity measurements, suggesting that this portion is influenced by tidal fluctuations. Fourteen sampling stations were established within this lateral range in order to examine the nutrient dynamics of the creek at various points in time. Our objective was to monitor potential changes in water quality conditions, especially on nutrients, in the creek during the day using the low and high tides as the predominating driver for the change. Temperature, pH, dissolved oxygen, conductivity and salinity were monitored bi-weekly at each station. Concentrations of dissolved nitrate (NO3), nitrite (NO2), ammonia (NH3), orthophosphate (PO4), alkalinity (Alk), and turbidity (Tbd) were measured at each station over the course of the field season. Average concentrations were generally low for the nitrogen species: NH4 = 0.11 mgL-1, NO3 = 0.30 mgL-1, NO2 = 0.02 mgL-1. Average alkalinity (92 mgL-1 CaCO3) and turbidity (71 FTU) concentrations were appropriate given the nature of the marsh environment. The average PO4 concentration, however, was elevated (=0.44 mgL-1). The EPA recommends values under 0.1 mgL-1 for this type of waterway. When considered separately, nutrient concentrations on outgoing tides were elevated relative to nutrient concentrations on incoming tides. Overall, the highest concentrations for all parameters occurred at low tide before the shift to the next incoming tide. This suggests that there are greater nutrient concentrations upstream than downstream. Given that land use in the Blackbird Creek watershed is primarily agricultural, it is likely that upstream pore water input from cropland is influencing the nutrient dynamics of the waterway. This information is key to understanding the efficiency of the riparian buffer system that has been established in the watershed and to allow for opportunities for improvement to mitigate nutrient runoff from agricultural fields.